Edukasi Kebijakan Perlindungan Data Kesehatan dalam Layanan Digital - Febri Febri; Awan Setiawan; Anisa Aulia (Lembaga Pengembangan Kinerja Dosen, 2024)
This community service activity aims to improve public understanding of health data protection policies in digital health services. The rapid development of digital health platforms has increased the risk of misuse and leakage of personal health data. The method used includes educational outreach, interactive discussions, and evaluation of participants’ understanding before and after the activity. The results show a significant improvement in participants’ awareness and knowledge regarding the importance of protecting personal health data and understanding applicable regulations. This activity contributes to strengthening digital literacy and encouraging safer use of digital health services. Participants also gained a deeper understanding of relevant laws and the potential consequences of data breaches. By empowering individuals with the necessary knowledge, the activity aims to mitigate the risks associated with digital health services, thus promoting a culture of privacy and security. This community service initiative highlights the vital role of education in fostering a safer digital environment for healthcare and safeguarding sensitive personal information from potential threats.